Bus Scheduling Simulation on Urban Routes Using Discrete Event Simulation Approach - Meliala, Najwa Aulia; Ferdiansyah Prayoga; Muhammad Kurniawan; M. Khalil Gibran (Yayasan Kita Menulis, 2025)
Efficient bus scheduling is a crucial element in urban transportation systems. This study aims to simulate a bus scheduling system on an urban route using the Discrete Event Simulation (DES) approach. The simulation models bus movement, passenger arrivals, and waiting times at each stop. The system consists of five bus stops and three buses operating on a fixed schedule. The simulation results indicate that passenger waiting times vary significantly across stops. The first stop shows the lowest waiting time, while mid- and end-route stops experience cumulative delays. The average waiting time can exceed 60 minutes at certain locations. Alternative scenarios involving additional buses show a notable decrease in waiting times and a significant improvement in scheduling efficiency. This study demonstrates that DES is an effective method for evaluating and designing adaptive and efficient transportation systems in urban environments.